Cortical gene expression correlates of temporal lobe epileptogenicity. Issue 3 (September 2016) - McCallum, Abigail P.; Gallek, Matthew J.; Ramey, Wyatt; Manziello, Ann; Witte, Marlys H.; Bernas, Michael J.; Labiner, David M.; Weinand, Martin E.
Abstract: Introduction: Despite being one of the most common neurological diseases, it is unknown whether there may be a genetic basis to temporal lobe epilepsy (TLE). Whole genome analyses were performed to test the hypothesis that temporal cortical gene expression differs between TLE patients with high vs. low baseline seizure frequency. Methods: Baseline seizure frequency was used as a clinical measure of epileptogenicity. Twenty-four patients in high or low seizure frequency groups (median seizures/month) underwent anterior temporal lobectomy with amygdalohippocampectomy for intractable TLE. RNA was isolated from the lateral temporal cortex and submitted for expression analysis. Genes significantly associated with baseline seizure frequency on likelihood ratio test were identified based on >0.90 area under the ROC curve, P value of <0.05. Results: Expression levels of forty genes were significantly associated with baseline seizure frequency. Of the seven most significant, four have been linked to other neurologic diseases. Expression levels associated with high seizure frequency included low expression of Homeobox A10, Forkhead box A2, Lymphoblastic leukemia derived sequence 1, HGF activator, Kelch repeat and BTB (POZ) domain containing 11, Thanatos-associated protein domain containing 8 and Heparin sulfate (glucosamine) 3-O-sulfotransferase 3A1. Conclusions: This study describes novel associations between forty known genes and a clinical marker of epileptogenicity, baseline seizure frequency. Four of the seven discussed have been previously related to other neurologic diseases. Future investigation of these genes could establish new biomarkers for predicting epileptogenicity, and could have significant implications for diagnosis and management of temporal lobe epilepsy, as well as epilepsy pathogenesis.